Animal pollination contributes to more than half of citrus production - Monasterolo, Marcos (2024)
Animal pollination is crucial for the reproduction and economic viability of a wide range of crops. Despite the existing data, the extent to which citrus crops depend on pollinators to guarantee fruit production still needs to be determined. Here, we described the composition of potential pollinators in citrus (Citrus spp.) from the main growing areas of Argentina; moreover, we combined Bayesian models and empirical simulations to assess the contribution of animal pollination on fruit set and yield ha−1 in different species and cultivars of lemons, grapefruits, mandarins, and oranges. Honeybee (A. mellifera L.) was the most commonly observed potential pollinator, followed by a diverse group of insects, mainly native bees. Regardless of citrus species and cultivars, the probability of flowers setting fruit in pollinated flowers was 2.4 times higher than unpollinated flowers. Furthermore, our simulations showed that about 60% of the citrus yield ha−1 can be attributable to animal pollination across all species and cultivars. Therefore, it is crucial to maintain environments that support pollinator diversity and increase consumer and to producer awareness and demand in order to ensure the significant benefits of animal pollination in citrus production.